THE DIFFERENT INTELLECTUAL TRENDS IN STUDYING THE THEORY OF ORGANIZATION AND THEIR ROLE IN THE THEORETICAL ROOTING OF THIS SPECIALIZATION - Khetam Dekhen Hamzah (Scholar Express Journals, 2022)
Through research, the researcher concluded that the business organization is one of the entities that were formed in order to carry out a commercial project. In this case, the business of the organization is governed by law systems such as contracts and property rights. These organizations usually take one of the following forms: sole proprietorship, partnerships, and limited liability companies, and through the research, it is clear that the theory of the organization is considered as a good principle and preserver of the organization’s position among the organizations and to maintain its position and position, in addition to the fact that the theory of the organization is the safe haven for the organization to maintain its work and activity, so the researcher presented in this research to address the issue of the theory of the organization, its concept, and its types, the information was presented in a simple way for the reader to enter it.
Keywords: simple; theory; organization; information